Dental and skeletal changes in patients with mandibular retrognathism following treatment with Herbst and pre-adjusted fixed appliance - Fabio de Abreu Vigorito; Gladys Cristina Dominguez; Luís Antônio de Arruda Aidar (Dental Press Editora, 2014)
OBJECTIVE: To assess the dentoskeletal changes observed in treatment of Class II, division 1 malocclusion patients with mandibular retrognathism. Treatment was performed with the Herbst orthopedic appliance during 13 months (phase I) and pre-adjusted orthodontic fixed appliance (phase II). METHODS: Lateral cephalograms of 17 adolescents were taken in phase I onset (T1) and completion (T2); in the first thirteen months of phase II (T3) and in phase II completion (T4). Differences among the cephalometric variables were statistically analyzed (Bonferroni variance and multiple comparisons). RESULTS: From T1 to T4, 42% of overall maxillary growth was observed between T1 and T2 (P < 0.01), 40.3% between T2 and T3 (P < 0.05) and 17.7% between T3 and T4 (n.s.). As for overall mandibular movement, 48.2% was observed between T1 and T2 (P < 0.001) and 51.8% between T2 and T4 (P < 0.01) of which 15.1% was observed between T2 and T3 (n.s.) and 36.7% between T3 and T4 (P < 0.01). Class II molar relationship and overjet were properly corrected. The occlusal plane which rotated clockwise between T1 and T2, returned to its initial position between T2 and T3 remaining stable until T4. The mandibular plane inclination did not change at any time during treatment. CONCLUSION: Mandibular growth was significantly greater in comparison to maxillary, allowing sagittal maxillomandibular adjustment. The dentoalveolar changes (upper molar) that overcorrected the malocclusion in phase I, partially recurred in phase II, but did not hinder correction of the malocclusion. Facial type was preserved.